2019
DOI: 10.5603/fm.a2018.0101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the factors associated with sublingual varices: a descriptive clinical study

Abstract: Background: Age is considered as an important factor for the development of sublingual varices (SV). It has been suggested that some other conditions such as gender, systemic diseases, smoking, denture wearing may play a role in aetiology. However, there are a limited number of studies investigating these associations. This study was perform to evaluate association between SV and the conditions which are described as possible risk factors previously. Materials and methods: A total of 691 patients (470 females,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 26 publications
7
45
1
Order By: Relevance
“…Same results were reported by other authors [19] that did not found any signi cant gender difference.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…Same results were reported by other authors [19] that did not found any signi cant gender difference.…”
Section: Introductionsupporting
confidence: 90%
“…The present study investigates a large number of risk factors in uencing the development of sublingual varices in a very large sample. Until now, only few studies focused the attention on the relation between SV and risk factors such as gender, age, diabetes mellitus, smoking and hypertension in a large population [10,19], without distinguish the different grade of hypertension. Thus, in our work, beside normotensive subjects, we examined three different hypertension situations, such as new diagnosed, resistant and compensated, clinically identi ed, excluding subjects presenting either masked hypertension or white coat syndrome [15][16][17][18] that could alter the blood pressure evaluation by using the ambulatory measurement along the 24-hour.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The normal variant in the oral mucosa is defined as a normal anatomical structure, with no pathological condition that can be found in the routine oral examination, but it can be misdiagnosed as a pathological condition. 1 Median rhomboid glossitis, 2 3 erythema migrants, 4 hairy tongue, 1 fissured tongue, 5 prominence of circumvallate papilla, 1 lingual varices, 6 and ankyloglossia 7 are the common normal variants that can be found in the dorsum and ventral of the tongue. Other variants such as pigmented fungiform papillae of the tongue and lingual fimbriae, which are rare conditions, are not widely reported and explained in the reference.…”
Section: Introductionmentioning
confidence: 99%